Efficiency of the State Corporations in Depressive Regions Development - Yuri Mikhailovich Tsygalov; Tatiyana Vitalievna Butova; Igor Igorevich Ordinartsev (Управленческое консультирование)
The transition to a market economy entailed the emergence of depressed regions, the development indicators of which lag significantly behind similar indicators in other regions of the country. Such regions are not able to generate the financial flows necessary for economic development. For the most part, such regions are not attractive for private business. A number of such regions is occupied by the North Caucasus Federal District. Subsidies of the federal budget reach 60% of local budgets in the region, which is 1.5 times higher than in other regions of the country. At the same time, the federal budget funds are primarily directed to support the social sphere but much less to develop the real sector of the economy. The share of the agrarian sector in the region’s economy reaches 22% while the average for Russia is 5%. The share of processing industries does not exceed 15%, while the average for the country is 19%. The region is characterized by extremely high unemployment, the level of which varies from 8% to 55% for the subjects of the federation included in the North Caucasus Federal District while the average for the country is 7%. The state is making certain efforts to raise the regional economy. Several programs for the development of the region and individual constituent entities have been developed. The disadvantage of all known programs is the poor financing of projects: 70-75% of the required funds should be provided by local budgets. World practice shows that for the development of depressed regions state corporations are effective, which are created to solve a specific problem and are endowed with broad powers and preferences, are provided with state funding. The paper proposes the framework conditions for the establishment of the Russian state corporation for the development of the NCFD and shows the potential effectiveness of the creation of such corporation.